Introducing Behavioral Wedges and Nudging Into the Production Process to Reduce CO2 : Frontløberne and the First Attempt to Create a CO2 Neutral Production in Denmark - Byrn, Whitney (Nordic Theatre Studies, 2023)
In January 2020, two actors in Denmark started an association, Bæredygtig Scenekunst NU (BS NU), dedicated to making theatre environmentally sustainable. Six weeks later, the country closed down due to COVID-19, and theatres closed. A few weeks later, Jacob Teglgaard from BS NU and Anne Gry Henningsen, Artistic Director of Mærkværk agreed that the play Frontløberne would be BS NU’s pilot project and proof of concept to test the policies and procedures BS NU hoped to eventually institute throughout the performing arts industry in Denmark. BS NU introduced behavioral wedges in the forms of an Environmental Policy, an Environmental Action Plan, and monitoring into the production process with the goal of nudging behavior to reduce emissions. In light of these behavioral wedges, this article will examine BS NU and Mærkværk’s journey of sustainability, the steps taken to create a sustainable production, elaborate the successes and failures of the process, and, most importantly, create a baseline CO2 figure for the production. Furthermore, it will discuss whether the behavioral wedges and nudging have led to shifting mindsets and long term behavioral changes that reduce CO2 emissions in theatrical production processes at Mærkværk.